2023
DOI: 10.5435/jaaosglobal-d-22-00286
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Six-Item Modified Frailty Index to Predict 30-day Adverse Events, Readmission, and Mortality in Older Patients Undergoing Surgical Fixation of Lower Extremity, Pelvic, and Acetabular Fractures

Abstract: Introduction:This is a retrospective study evaluating the use of a new six-item modified frailty index (MF-6) to predict short-term outcomes of patients receiving surgery for lower extremity fractures.Methods:Patients older than 65 years undergoing open reduction and internal fixation for lower extremity, pelvic, and acetabulum fractures were identified from the American College of Surgeons National Surgical Quality Improvement Program. The MF-6 was calculated by assigning one point for each of six common cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…A study by Pean et al investigated MF-6 as a predictor for short-term adverse events following lower extremity open reduction and internal fixation and found that a high MF-6 score was associated with higher rates of infectious complications, readmission, and non-home discharge. 12 The results of our study are consistent with those by Pean et al, as we also found MF-6 ≥3 to be associated with UTI, readmission, and non-home discharge. However, while Pean et al found an association between MF-6 and mortality, we did not find an association with mortality following TSA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A study by Pean et al investigated MF-6 as a predictor for short-term adverse events following lower extremity open reduction and internal fixation and found that a high MF-6 score was associated with higher rates of infectious complications, readmission, and non-home discharge. 12 The results of our study are consistent with those by Pean et al, as we also found MF-6 ≥3 to be associated with UTI, readmission, and non-home discharge. However, while Pean et al found an association between MF-6 and mortality, we did not find an association with mortality following TSA.…”
Section: Discussionsupporting
confidence: 93%
“… 7 The Modified Frailty Index originally included 11 items that was simplified to 5 items (diabetes mellitus, CHF, COPD or current pneumonia, hypertension requiring medication, and dependent functional status). 12 The modified 5-item frailty index was shown to retain its predictive power for frailty compared to the original 11-item frailty index. 16 Recently an MF-6 has gained popularity, which includes hypoalbuminemia as the sixth item.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using the 6-Item Modified Frailty Index (MF-6), Pean et al investigated the impact of frailty on patients with pelvic fractures, as well as other lower extremity fractures, undergoing surgical fixation. Their comprehensive analyses not only underscored the association of frailty with heightened mortality risk, major adverse events, readmission, and non-home discharge, but also with an extended length of stay [ 39 ].…”
Section: Discussionmentioning
confidence: 99%